2022
DOI: 10.1093/jopart/muac022
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction and Citizen Satisfaction with Street-level Bureaucrats: Is There a Satisfaction Mirror?

Abstract: It is often argued that employees satisfied with their jobs perform better, which in turn will lead customers to be more satisfied. Private sector studies have found support for this “satisfaction mirror” hypothesis. Our study is the first to provide direct, individual-level evidence of its existence in the public sector. We conducted an original survey of village officials in small, rural Chinese villages, and local citizens interacting with them. Village officials are charged with delivering nearly all types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…This probably explains why a considerable percentage of respondents assume their agency practices the more deliberative form of participation where decision-making authority is shared or even granted to the public. Future research could use survey experiments such as list experiments to overcome this issue (Kim & Kim, 2017; Petrovsky et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This probably explains why a considerable percentage of respondents assume their agency practices the more deliberative form of participation where decision-making authority is shared or even granted to the public. Future research could use survey experiments such as list experiments to overcome this issue (Kim & Kim, 2017; Petrovsky et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we categorized these antecedents into three overarching groups: environmental, organizational, and individual-level factors, as presented in Table 5. Outsourcing (Dahlström et al, 2018;Holum, 2018, Hong, 2017 Cooperation, consolidation (Holum & Jakobsen, 2016;Ma, 2017) Reform (Grosso & Van Ryzin, 2012;Pitia et Poister & Thomas, 2011;Porumbescu, 2017b;Van Ryzin, 2004, 2006Zhang et al, 2022) Disconfirmation (Abdelkarim, 2023;Filtenborg et al, 2017;Grimmelikhuijsen & Porumbescu, 2017;Poister & Thomas, 2011;Van Ryzin, 2004, 2006 Performance treatments (Abdelkarim, 2023;Filtenborg et al, 2017;Grimmelikhuijsen & Porumbescu, 2017) Perceived/experienced performance (Andersen & Hjortskov, 2016;James, 2009;Poister & Thomas, 2011;Song et al, 2020;Van Ryzin, 2006Zhang et al, 2022) Performance minus expectation (James, 2009;Noda, 2021Petrovsky et al, 2017Petrovsky et al, 2023) Importance 36 (10.9%) Perceived importance of services ) Attitudes toward government 22 (6.7%) Trust in government (Ariely, 2013;Mishra & Momin, 2020;Park & Blenkinsopp, 2011;Porumbescu, 2017a;Van Ryzin, 2004;…”
Section: Antecedents Of Citizen Satisfactionmentioning
confidence: 99%
“…This strand of thesis indicates that when a citizen's experience with public service provision is largely positive, he or she is likely to appreciate the competency of the provider—government and therefore place trust in it (Bok, 1997; Cook et al., 2010; He and Ma, 2021; Petrovsky et al., 2022). Scholars have suggested that knowledge about the performance could increase or decrease trust in the government (Bok, 1997; Cook et al., 2010; Hibbing and Theiss‐Moore, 2001).…”
Section: Citizen Participation Perceived Performance Satisfaction And...mentioning
confidence: 99%
“…Because citizen satisfaction is an important indicator of the success of government policies and decisions (Sun and van Ryzin, 2014), it is of great instrumental significance to the government in accomplishing professional and institutional objectives (van Ryzin, 2007; Petrovsky et al., 2022). However, the literature sees no conclusive findings regarding the relationship between citizens’ satisfaction with the government and their trust in the government.…”
Section: Citizen Participation Perceived Performance Satisfaction And...mentioning
confidence: 99%